The Effect of Foliar Spraying of Plant-Derived Smoke in Different Stages of Growth on Quantitative and Qualitative Yield of Safflower (Carthamus tinctorius L.) - Douaa Heydar Mehdi; Saeed Jalali Honarmand (Journal of Global Innovations in Agricultural Sciences)
This experiment was conducted in a factorial design using a randomized complete block design with three replications at a research farm in Babylon, Iraq, located at coordinates (32º 24ʹ 07ʺ N and 44º 43ʹ 22ʺ E). The study was carried out over two consecutive years, 2021 and 2022, focusing on safflower. The first factor examined different concentrations of plant-derived smoke (0.5, 1, and 1.5 liters per hectare), with normal water as the control. The second factor involved foliar spraying at various growth stages: 1) emergence, 2) stem elongation, 3) flowering, 4) emergence + stem elongation, 5) emergence + flowering, 6) stem elongation + flowering, and 7) emergence + stem elongation + flowering. The results indicated that foliar spraying with plant-derived smoke at different growth stages significantly affected various traits of safflower plants. Increasing the concentration of smoke water resulted in significant increases in the number of leaves per plant, number of heads per plant, number of seeds per head, biological yield, grain yield, oil yield, and stem diameter in comparison to the control group, except for a decrease in leaf temperature. However, the plant-derived smoke applied at multiple growth stages had a more significant positive effect than single-stage applications. The highest grain yield (3,604 kg/ha; P<0.05), oil percentage (23.07%), and oil yield (873.7 kg/ha) were achieved by applying 1.5 L/ha of plant-derived smoke during the seedling, stem elongation, and flowering stages. In conclusion, utilizing plant-derived smoke at various growth stages can enhance both the quantitative and qualitative yield of safflower. The results indicate that foliar spraying with plant-derived smoke, particularly at higher concentrations and during multiple growth stages, can be an effective method for enhancing safflower productivity. Keywords: Growth stage, foliar spraying, safflower, smoke-water, agricultural productivity, Iraq.